2012
DOI: 10.1111/j.2042-7158.2011.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the molecular pharmacology of the serotonergic system: using fluoxetine as a model

Abstract: Keywords AbstractObjectives Serotonin is a monoamine neurotransmitter that is widely distributed in the body and plays an important role in a variety of psychological and other body functions such as mood, sexual desire and function, appetite, sleep, memory and learning, temperature regulation and social behaviour. This review will assess the use of fluoxetine, one of the most commonly used selective serotonin reuptake inhibitors, as a model for understanding the molecular pharmacology of the serotoninergic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 45 publications
0
28
0
5
Order By: Relevance
“…It blocks serotonin transporter protein by high-affinity mechanism and increases the concentration of this mediator in the central nervous system (CNS) and peripheral tissues. 3 Experimental data showed that along with its main pharmacological effect -antidepressivefluoxetine has ant-inflammatory activity. 4 Studies on the anti-inflammatory activity of antidepressants are of interest in several areas.…”
Section: Introductionmentioning
confidence: 99%
“…It blocks serotonin transporter protein by high-affinity mechanism and increases the concentration of this mediator in the central nervous system (CNS) and peripheral tissues. 3 Experimental data showed that along with its main pharmacological effect -antidepressivefluoxetine has ant-inflammatory activity. 4 Studies on the anti-inflammatory activity of antidepressants are of interest in several areas.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in 1974 (Wong et al, 1974), the beneficial psychotropic effects of fluoxetine have led to its being used to treat disorders other than depression, including obsessive compulsive disorders and bulimia nervosa (Wong et al, 1995). The multiple side effects of fluoxetine (Sghendo and Mifsud, 2012) have raised questions about its supposed selective serotonin-mediated effect. Fluoxetine inhibits the serotonin transporter (SERT) in the low nanomolar range (Torres et al, 2003), but its therapeutic effect appears only at much higher plasma and brain concentrations (Muscettola et al, 1978;Bolo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One of the degradation pathways of serotonin is performed by the enzymes monoamine oxidase A and B, breaking down serotonin into 5-hydroxyindoleacetic acid [21]. A second mechanism of serotonin degradation regards its reuptake by its transporter, located in the pre-synaptic membrane [22]. SERT is the main agent responsible for the regulation of 5-HT levels in the synaptic gap.…”
Section: Serotoninergic System and Developmentmentioning
confidence: 99%
“…The function of this cell membrane protein is to reuptake 5-HT that has not been broken down by monoamine oxidase in the synaptic gap and transfer it to the inside of the pre-synaptic neurons [22]. Active removal increases the speed in which the levels of neurotransmitter in the synaptic gap decrease, restricting the effects of 5-HT to smaller areas, and recycles some of the neurotransmitter relased in the synapse for later use [22]. By changing its conformation, SERT moves one or more serotonin molecules per cycle, unlike transmembrane channels, which remain open or closed.…”
Section: Serotoninergic System and Developmentmentioning
confidence: 99%
See 1 more Smart Citation